Institutionalization / deinstitutionalization of people with disabilities a contemporary social problem - Nina Stănescu (Technium Social Sciences Journal, 2020)
In contemporary society, although many adolescents with disabilities are making social integration efforts, many of them are unemployed. Unemployment officially and open refers to direct exclusion from the labor market, but there is also a phenomenon of exclusion inside the labor market. Some groups are involved in segments where jobs are uncertain, poorly paid and do not require special or specialized training. Labor market segmentation tends to be built around immediately identifiable groups (eg by age, ethnicity, gender), so that the exclusion of the "decency" is doubled, associated with other forms of social exclusion. It is necessary to improve social policies in the field of disabled people and the strengthening of strategies in the development process of institutionalization of disabled adults.